2022
DOI: 10.1037/bne0000484
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in conditioned orienting and the role of estradiol in addiction-related behaviors.

Abstract: Conditioned orienting response (OR) is a form of cue-directed behavior thought to indicate increased attentional and/or motivational processing of reward-associated stimuli. OR as a phenotype has been shown to predict both direct drug proclivity in female rats and behaviors indirectly related to drug proclivity in male rats, but no extant research has compared males and females in terms of their OR behavior or its notable substrates. As females are at increased risk for substance abuse, and the ovarian hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…We also expected a poor performance in the light discrimination task by the control proestrus female rats, as a previous study demonstrated impaired set-shifting performance in ovariectomized female rats with 17β-estradiol treatment (Hilz et al, 2022 ). It is important to note that our results contradict two other studies, which are carried out on female rhesus monkeys and female rats, respectively, and showed that estradiol treatment improves set shifting (Voytko et al, 2009 ; Lipatova et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We also expected a poor performance in the light discrimination task by the control proestrus female rats, as a previous study demonstrated impaired set-shifting performance in ovariectomized female rats with 17β-estradiol treatment (Hilz et al, 2022 ). It is important to note that our results contradict two other studies, which are carried out on female rhesus monkeys and female rats, respectively, and showed that estradiol treatment improves set shifting (Voytko et al, 2009 ; Lipatova et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…It is important to consider where women are in their cycle when exposed to stress and cognitive flexibility testing, as gonadal hormones can contribute to sex differences in response to stress (Becker et al, 2005 ; Oyola and Handa, 2017 ; Heck and Handa, 2019 ). Although previous studies have separately examined sex differences in cognitive flexibility (LaClair et al, 2019 ; Hilz et al, 2022 ), stress effects on cognitive flexibility (Thai et al, 2013 ; Hurtubise and Howland, 2016 ; Shields et al, 2016 ; Goldfarb et al, 2017 ; Grafe et al, 2017a ; Sullivan et al, 2019 ), and the effect of gonadal hormones on cognitive flexibility (Wallin and Wood, 2015 ; Lipatova et al, 2016 ; Hilz et al, 2022 ), many of the findings were inconsistent, and the role of the estrous cycle in stress-induced impacts on cognitive flexibility is still unknown. This study explored sex differences in cognitive flexibility using an operant strategy-shifting paradigm after either control conditions or restraint stress in freely cycling female and male rats (with estrous cycle tracking in the female rats).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…USVs were recorded throughout CPP procedures for a subset of rats ( n = 28; 5 rats did not have USV recording) and digitized with UltraSoundGate system (Avisoft Bioacoustics) using methods described in Hilz et al, 2021. USVs were recorded and analyzed using Avisoft-RECORDER and Avisoft-SASlab Pro software (Avisoft Bioacoustics).…”
Section: Methodsmentioning
confidence: 99%